2021
DOI: 10.3389/fped.2021.599730
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Growth Velocity Among School Age Children With Different Body Mass Index From Childhood Into Early Adolescence in Hualien County, Taiwan: A Retrospective Cohort Study

Abstract: Objective: This study aimed to investigate the contribution of high body mass index (BMI) to growth velocity among school-aged children who remained in the same BMI categories for a 6-year period.Methods: This retrospective cohort study included children who enrolled in the school year 2009 and remained in the same BMI categories during their 1st, 4th, and 7th grades (6–7, 9–10, 12–13 years of age). Annual linear growth velocity and weight gain were calculated and compared between sexes, BMI groups, and differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The quality of the eaten food was associated with a risk of obesity: fruit was inversely associated with the risk of obesity; on the contrary, sweetened beverages and refined carbohydrates with added fat were associated with increased risk of obesity ( 26 ). Hsiao et al ( 28 ) mentioned that to achieve good family health, physicians should engage the concerns of parents to empower their knowledge of healthy literacy in nutrition, exercise, and parenting skills. A family-based exercise plan, healthy diet plan, and structural daily schedule will provide a supportive environment for children after leaving the school campus.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of the eaten food was associated with a risk of obesity: fruit was inversely associated with the risk of obesity; on the contrary, sweetened beverages and refined carbohydrates with added fat were associated with increased risk of obesity ( 26 ). Hsiao et al ( 28 ) mentioned that to achieve good family health, physicians should engage the concerns of parents to empower their knowledge of healthy literacy in nutrition, exercise, and parenting skills. A family-based exercise plan, healthy diet plan, and structural daily schedule will provide a supportive environment for children after leaving the school campus.…”
Section: Discussionmentioning
confidence: 99%
“…A study taken from an obesity clinic explored the association between obesity and height throughout childhood and adolescence (17); the obese subjects were taller than average in childhood, but the growth advantage gradually decreased and the final adult height of obese and normal subjects was equal. A recent Taiwan cohort study (19) also illustrated that obese subjects between 9 and 13 years of age tended to have higher linear growth velocity than subjects with normal BMI. However, the Swedish population-based longitudinal growth study (18) concluded that overnutrition between 2 and 8 years of age will not be beneficial from a final height point of view, as the temporary increase in height gain will be compensated by an earlier pubertal maturity and a subnormal height gain in adolescence.…”
Section: Discussionmentioning
confidence: 96%
“…However, these data were based on inpatient or outpatient series, and the number of subjects was relatively small. Several cohort studies have demonstrated that growing up in a state of obesity demonstrated a smaller growth spurt during puberty, leading to an impaired final height (17)(18)(19). However, some of the series were taken from the obesity clinic, and most of the studies made the evaluation based on BMI measurement.…”
Section: Introductionmentioning
confidence: 99%
“…A study examining the growth velocity among school-aged children with different BMI categories found that obesity was associated with higher annual weight gain and height gain between 6 and 13 years of age. However, overweight and obese girls between 9 and 13 years of age had less linear growth velocity than underweight girls at the same interval, suggesting that puberty may have a greater influence on growth velocity than BMI in girls entering pubertal age [8].…”
Section: Introductionmentioning
confidence: 94%